Decolonising Solidarity? : 50 Years of the Transnational Mapuche Advocacy Network (Alternautas, 2024)
While the 50th anniversary of the coup d’état against the government of Salvador Allende in Chile invites to reflect on past and current experiences of solidarity between Latin America and Europe, the present contribution seeks to foreground the rather overlooked international solidarity efforts of and with the indigenous Mapuche. As a result of their forced exile to Europe after 1973, Mapuche activists began to organise themselves as a diasporic community in Europe and to form a transnational advocacy network in support of their people. This contribution aims to showcase how international solidarity of and with the Mapuche in Europe evolved over time, how they relate to non-indigenous, Chilean solidarity networks, and which underlying Mapuche notions of solidarity they reactivate in order to weave their transnational advocacy network.